2022
DOI: 10.1039/d2fo01343f
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin peptide Asp-Gln-Trp alleviates hepatic insulin resistance and modulates gut microbiota dysbiosis in high-fat diet-induced NAFLD mice

Abstract: The progression of nonalcoholic fatty liver disease (NAFLD) is closely related to insulin resistance and gut microbiota. Dietary interventions have emerged as effective palliative strategies for NAFLD. The present study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 67 publications
(90 reference statements)
6
31
0
Order By: Relevance
“…Muribaculaceae is the producer of SCFAs such as succinic acid, acetic acid, and propionic acid, which have important anti-inflammatory properties as well as effects on glucose and lipid homeostasis (53). Moreover, several studies have confirmed a positive correlation between the increased abundance of Muribaculaceae and improvement in NAFLD (54,55). Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators.…”
Section: Discussionsupporting
confidence: 91%
“…Muribaculaceae is the producer of SCFAs such as succinic acid, acetic acid, and propionic acid, which have important anti-inflammatory properties as well as effects on glucose and lipid homeostasis (53). Moreover, several studies have confirmed a positive correlation between the increased abundance of Muribaculaceae and improvement in NAFLD (54,55). Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators.…”
Section: Discussionsupporting
confidence: 91%
“…6(b), the community structures of HF02‐H and the ND groups were different from that of the HFD group, indicating that LP‐HF02 changed intestinal microbiota structure of obese mice. Thus, our results demonstrated that LP‐HF02 treatment improved the community richness and community structure of intestinal microbiota in obese mice, thereby increasing the microbiota resilience 36,37 …”
Section: Resultsmentioning
confidence: 54%
“…When intestinal permeability is increased, LPS can penetrate the intestinal barrier and enter into the blood, causing endotoxemia and subsequently contributing to the production of inflammatory cytokines (including IL‐1β and TNF‐α) 36 . Systemic inflammation will speed up the catabolism of TG in adipose tissue, resulting in excess FFAs influx into the liver, leading to hepatic lipids ectopic accumulation, thereby exacerbating the development of obesity 25,37 . Our data showed that the levels of serum LPS, IL‐1β and TNF‐α in obese mice were elevated by 2.10‐fold, 2.23‐fold, and 2.16‐fold, respectively, compared with the ND group, whereas LP‐HF02 remarkedly reversed these trends (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Our results consistently revealed that Alloprevotella was enriched by MCE supplementation, and a significant decrease in abundance of Bilophila, unclassified_f_Lachnospiraceae , unclassified_f_Oscillospiraceae , and norank_f_Oscillospiraceae was observed in the MCE group compared to the HFD group ( Figure S1 ). Moreover, the abundance of norank_f_Muribaculaceae and Lachnospiraceae_NK4A136_group has been believed to be negatively associated with the development of obesity [ 35 , 36 ]. However, in the present study, we observed that the supplementation of MCE induced a decreased abundance of norank_f_Muribaculaceae and Lachnospiraceae_NK4A136_group .…”
Section: Discussionmentioning
confidence: 99%